Penerapan target costing dengan pendekatan activity-based costing pada UD. Monicha Jaya - Tiow, Angelica Gabriela; Kalalo, Meily Y. B.; Mintalangi, Syermi S. E. (Manajemen Bisnis dan Keuangan Korporat, 2025)
Target costing is a method used to encourage various departments involved in product design and production to find more efficient ways to achieve superior product quality. Meanwhile, from a managerial perspective, activity-based costing provides information on all activities related to product manufacturing and their associated costs. With this information, management can focus on activities that offer opportunities for cost savings. This study aims to examine the application of target costing using the activity-based costing approach in the cakalang floss business, UD. Monicha Jaya, and to compare different methods of determining production costs as an alternative for cost control. The research employs a descriptive qualitative approach, with data collected through observation, interviews, and documentation. The results indicate that the activity-based costing method provides a significantly more efficient calculation of production costs compared to traditional methods.